БИОЛЮМИНЕСЦЕНЦИЯ ОКЕАНА: ИСТОРИЯ ИССЛЕДОВАНИЙ, РАЗВИТИЕ МЕТОДИЧЕСКОЙ БАЗЫ, НЕРЕШЕННЫЕ ПРОБЛЕМЫ - (:unkn) unknown (Севастополь: ЭКОСИ-Гидрофизика, 2006)
Представлен краткий исторический обзор исследований биолюминесценции Мирового океана. Описана история развития техники и методологии исследования биолюминесценции как универсального экспресс-маркёра планктонного сообщества. Приведены уникальные сведения о необъясненных до настоящего времени случаях биолюминесценции, которые представляют несомненный интерес в плане перспективных направлений исследований жизни океана.
OCEAN BIOLUMINESCENCE: HISTORY OF INVESTIGATIONS, DEVELOPMENT OF THE METHODICAL BASE, UNRESOLVED PROBLEMS
The brief historical review of the World ocean bioluminescence studies has been presented. History of development of the technique and methodology of the bioluminescence studying as universal express-marker for the plankton community has been described. Unique data on unexplained to the present time cases of bioluminescence, which are of great interest in consideration of perspective directions in the ocean life investigations have been given.